The role of gut-brain axis in neurodegenerative diseases - Yory-Montalvo, Nicolás (2023)
In recent years, the role of the microbiota in the digestive tract and its relationship with the central nervous system has been heavily researched, in what is known as the gut-brain axis, establishing bidirectional interactions. Scientific studies have provided data that contribute to the understanding of this axis, which appears to be maintained through connections via the vagus nerve and through the circulatory system, through which neurotransmitters, hormones, cytokines, and other metabolites, including toxins, can be released and spread. These communication systems are influenced by the composition of the microbiota, which, in turn, is affected by central processes. All these processes involve the immune system, which intimately interacts with the enteric nervous system and the gut. Although these mechanisms have not been fully elucidated, this axis is proposed as a possible pathological basis for numerous neurological disorders of great impact, such as Alzheimer's disease, Parkinson's disease, and epilepsy. This review gathers information from recent studies that support and contribute to the description of the involvement of the brain-gut axis in the development of these neurodegenerative conditions.